Program Penurunan Tingkat Kehilangan Air Perum Muria Indah PDAM Kabupaten Kudus - Awaluddin Setya Aji; R. Gagak Eko Bhaskoro; Nitis Aruming Firdaus (Universitas Prof. Dr. Hazairin, S.H, 2018)
Non Revenue Water (NRW) of Regional Water Company (PDAM) in Kudus Regency is included in the high category. Both direct and indirect water loss will affect the availability of sufficient water for people needs (Quantity), the availability of water that meets quality of the health requirements (drinking water/clean water) (Quality) and the availability of permanent water with adequate pressure for people needs. The methods used in handling this water loss were Water Balance Zero, Water Balance One, ILI -0 and ILI -1. The percentage of leakage reduction in the researched area is 8%: from 49% (WB-0) to 41% (WB-1)